Philippine multilingual medical thesaurus on diseases - pathological conditions, signs, and symptoms in Waray - Balanquit, Loiue Stihl L.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2015)
This study was conducted to translate MeSH terms on Diseases: Pathological conditions, signs and symptoms into Waray to become part of the Philippine Multilingual Medical Thesaurus.
The medical terms were obtained from the Medical Subject Headings (MeSH) browser which is available online. The terms came from the Category C23 - Disease: Pathological conditions, signs and symptoms. These terms were initially translated through the use of the ranked dictionaries: Binisaya-English English- Binisaya Dictionary by Eduardo A. Makabenta and Eduardo T. Makabenta, Jr.; and Dictionary: English, Waray-waray, Tagalog by Tomas A. Abuyen. Supplementary tools were also used for validation and cross-checking purposes.
The researcher interviewed 5 respondents who are in the field of medicine and allied health sciences (i. e. medical practitioners; and 5 respondents who are non-medical practitioners). They provided translation terms which the researcher used to analyze and compare with the initially translated terms through triangulation.
The rules and policies from the standards and guidelines on thesaurus construction that were used in this study came from foreign and local resources. The translated terms were arranged alphabetically so end-users can easily search and browse through the thesaurus.
The study was able to translate 129 terms or 15.14% have Waray terms equivalent, 20 or 2.35% have no equivalent translation but have a scope note, and 82.51% have neither equivalent Waray translation nor scope notes.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Waray -- Diseases; Waray language -- Medical Waray; Subject headings -- Waray -- Medicine